Depiction of Vaginal Microbiota in Women With High-Risk Human Papillomavirus Infection - Wei, Zhen-Tong; Chen, Hong-Liang; Wang, Chun-Feng; Yang, Gui-Lian; Han, Shu-Mei; Zhang, Song-Ling (Frontiers in Public Health, 2021)
Persistent infection with the carcinogenic human papillomavirus (HPV) is a prerequisite for the progression of cervical lesions and cancer. A growing body of research has focused on the functional role of the vaginal microbiota in the persistence of HPV infection. Understanding the microbial composition and structure in women with high-risk (hr)-HPV infection may help reveal associations between the vaginal microbiota and HPV infection, and identify potential biomarkers. Our study investigated the vaginal microbial community in women with and without hr-HPV infection, by using 16s rRNA gene sequencing. We found that microbial perturbations occurred in the early phase of hr-HPV infection. Lactobacillus and Sporolactobacillus were decreased, while bacteria related to bacterial vaginosis (BV), such as Gardnerella, Prevotella, Dialister, Slackia, Actinomyces, Porphyromonas, Peptoniphilus, Anaerococcus, Peptostreptococcus, Streptococcus, Ureaplasma, Megasphaera, and Mycoplasma were increased. Our results could offer insights into the correlations between hr-HPV and the vaginal microbiota in the early infection period, and provide indications that the predominance of some BV-associated bacteria during hr-HPV infection may increase the risk for cervical neoplasia.